Drivers and Barriers Toward Healthy and Environmentally Sustainable Eating in Switzerland: Linking Impacts to Intentions and Practices - Baur, Ivo; Stylianou, Katerina S.; Ernstoff, Alexi; Hansmann, Ralph; Jolliet, Olivier; Binder, Claudia R. (Frontiers in Sustainable Food Systems, 2022)
Food consumption is among the activities with the most significant environmental impacts, and furthermore contributes to rising health costs. We explored the factors that foster or hinder healthy and sustainable eating in Switzerland. Based on an online household survey with 620 respondents, we first determined the disability adjusted life years and greenhouse gas impacts associated with individuals' dietary habits to measure healthy and environmentally sustainable eating. We then relate the nutritional health and environmental impacts to individual's intentions, and explore what interpersonal and societal factors foster or hinder healthy and sustainable eating. Results suggest that intentions for healthy eating are stronger than intentions to eat environmentally sustainable and that intentions for healthy eating transmit better into behavior than intentions for environmentally sustainable eating. Males and females had similar intentions but males showed substantially higher dietary related health impacts with 12 min of healthy life lost per day and 14% higher carbon footprint than females. Furthermore, vegan and vegetarian diets yielded very high nutritional health benefits of >23 min of healthy life gained per person and day, mostly realized through the reduced intake in processed and red meat and increased consumption of nuts, wholegrain, and to a lesser extent in fruits and vegetables. Meatless diets show concurrent high reductions in the carbon footprint of −42% for vegetarians and −67% for vegan. A key obstacle to healthier and more environmentally sustainable eating is that people do not recognize the high nutritional and environmental co benefits of vegetarian and vegan diets. This suggests that policies promoting healthy eating can target factors affecting intentions, while measures targeting environmentally sustainable eating should aim at overcoming the intention behavior gap, by informing on e.g. the importance of reducing meat consumption toward environmental sustainability.